2019
DOI: 10.1038/s41598-018-35744-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of recombinant glutamic acid decarboxylase in insect larvae and its application in an immunoassay for the diagnosis of autoimmune diabetes mellitus

Abstract: Autoimmune Diabetes Mellitus (DM) is a chronic disease caused by the selective destruction of insulin producing beta cells in human pancreas. DM is characterized by the presence of autoantibodies that bind a variety of islet-cell antigens. The 65 kDa isoform of glutamate decarboxylase (GAD65) is a major autoantigen recognized by these autoantibodies. Autoantibodies to GAD65 (GADA) are considered predictive markers of the disease when tested in combination with other specific autoantibodies. In order to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Previous studies have shown inefficient secretion of some other recombinant glycoproteins produced by BEVS (Klaus et al 2015;Trabucchi et al 2019). However, the fact that the expressed protein remained inside the cells did not affect its production and recovery.…”
Section: G E Expression and Localization In Sf9 Cellsmentioning
confidence: 91%
“…Previous studies have shown inefficient secretion of some other recombinant glycoproteins produced by BEVS (Klaus et al 2015;Trabucchi et al 2019). However, the fact that the expressed protein remained inside the cells did not affect its production and recovery.…”
Section: G E Expression and Localization In Sf9 Cellsmentioning
confidence: 91%
“…The chimera cassette was directly cloned under the polyhedrin (polh) promoter using the EcoR1 and XbaI site, into the pFastBac Dual vector (Thermo Fisher Scientific), previously modified with the enhanced green fluorescent protein (EGFP) cDNA under the p10 promoter (Targovnik et al, 2019). The final construction pFBD-p10-EGFP-polh-ZnT8/GAD65 is shown in Figure 1.…”
Section: Recombinant Virus Constructionmentioning
confidence: 99%
“…After 4 days of incubation in the dark at 27 degC, in continuous agitation, cells were centrifuged. The recombinant chimera was recovered following the protocols of lysis and purification previously described by our group (Trabucchi et al, 2019).…”
Section: Recombinant Znt8/gad65 Expression and Purification From Cell...mentioning
confidence: 99%
See 2 more Smart Citations